Perlakuan Pupuk Daun dan Fungisida terhadap Intensitas Penyakit Phyllosticta dan Hasil Tanaman Jahe (Zingiber officinale): Effect of Foliar Fertilizer and Fungicide Application on Intensity Attack of Phyllosticta zingiberi and yield of ginger (Zingiber officinale) - Annisa Khoiriyah; Heriyanto; Fitria Naimatu Sa'diyah (Jurnal Agroekoteknologi dan Agribisnis, 2023)
T Phyllosticta zingiberii is the dominant cause of leaf spot disease in Indonesia. Leaf spot disease is the potential to cause great losses to ginger production. The research objectives were to investigate the dosage of fungicide and foliar fertilizer which are effective for controlling Phyllosticta zingiberi leaf spot disease of ginger. The research was conducted in Argodadi, Sedayu, Bantul, DIY and arranged in factorial design in a complete randomized block design that consists of two factors. The first factor is the application dose of fungicide, which consists of three levels, namely 0 g/L, 1,5 g/L, and 3 g/L. The second factor is the application dose of foliar fertilizer, which consists of three levels, namely 0 cc/L, 2,5 cc/L, and 5 cc/L The result of the research provides information that the application of 3 g/L fungicide is more effective in reducing the percentage and the intensity attack of Phyllosticta zingiberi effectively by 56,03 and 65,90%. Applying fungicide at the level of 3 g/l and 5 ml/l of foliar fertilizer was more effective in increasing ginger rhizome’s growth and productivity.